Digitrajnost zahteva digipismenost - Klajnšek, Aljanka (Uporabna informatika (Ljubljana), 2023)
The Republic of Slovenia has decided in its strategic development documents that it wants to build its development sustainably and with the help of digitization. However, insufficient attention is paid to some key requirements that must be met for such a transition. One of them is (digital) literacy of the population, which can be achieved through lifelong learning. The purpose and desired effect of the concept of lifelong learning is to create an environment in which individuals, in an era of rapid and major technological changes, develop their skills for an independent and active life and integration into society throughout their lives. The Court of Audit of the Republic of Slovenia carried out an audit in which it addressed the implementation of lifelong learning in the Republic of Slovenia with an emphasis on adults. The aim of the audit was to establish whether the Republic of Slovenia is effective in enforcing lifelong learning as a social development strategy. This article presents findings of the audit and focuses on the importance of lifelong learning and availability of data on the skills of the population for a realistic assessment of competences in the Republic of Slovenia required for a transition to a digital and sustainable society. It concludes with some recommendations for improvement.
Keywords: Court of Audit of the Republic of Slovenia; digital literacy; digital transformation; digitalna pismenost; digitalna preobrazba; lifelong learning; Računsko sodišče Republike Slovenije; sustainable development.; trajnostni razvoj; vseživljenjsko učenje